2017
DOI: 10.4236/psych.2017.84036
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors and Quality of Life in Children and Adolescents under Cancer Treatment

Abstract: The evaluation of quality of life in children and adolescents with cancer has become an increasing necessity, because of the different areas of the patient's and its families lives that get affected by this disease. The aim of this research was to determine the association between quality of life and sociodemographic variables in children and adolescents with cancer and their families. We developed a transversal and analytic study that included a sample of fifty-nine patients from four to 16 years old, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It is also evident that the variables associated with OHRQOL impact in RA patients are erosive RA and perceiving morning stiffness, both being risk factors. 38 Results were similar to those who reported fatigue and depression. In a study carried out on women with RA, the tendency was to be more vulnerable and less optimistic when the presence of daily pain was experienced.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is also evident that the variables associated with OHRQOL impact in RA patients are erosive RA and perceiving morning stiffness, both being risk factors. 38 Results were similar to those who reported fatigue and depression. In a study carried out on women with RA, the tendency was to be more vulnerable and less optimistic when the presence of daily pain was experienced.…”
Section: Discussionsupporting
confidence: 76%
“…Comparable results have been reported by other researchers. 38 When inquiring if the patients received alternative treatment -apart from the conventional one -such as homeopathy, bioenergetics, and natural treatments, among others, we found that only one person answered in the affirmative. People who answered in the negative reported the highest impact scores on the OHIP-14.…”
Section: Discussionmentioning
confidence: 89%
“…Deterioration of QoL in pediatric cancer patients was often attributed to painful clinical interventions, surgery, intensive chemotherapy, and hospitalization. Existing literature indicated that the physical, emotional, and social dimensions of the QoL of children with cancer differed according to various demographic factors, e.g., age [7] and gender [8], as well as disease and treatment-related factors, e.g., diagnosis, duration, and the type of treatment [9]. Specifically, children, as compared with adolescents, reported lower QoL for the initial period after diagnosis.…”
Section: Introductionmentioning
confidence: 99%